Simulation of biocomposites through biomimetic of hierarchical structures - Choong, Wei Wei (2014)
Over the recent years, the number of osteoporotic fractures has been on the rise. With the advances in medical science, patients are able to undergo surgeries to get the fractured parts replaced. However, the drawback of this treatment is that the patients usually suffers from stress shielding; this means that the bone tissues are not receiving enough loads or stress and the bone materials are reabsorbed by the body at the area where the bone and implant connects; the implant then becomes loose and fail as a result. The aim of this study is to simulate a biocomposite made from polymer and ceramic by mimicking hierarchical structures of natural materials. ANSYS APDL was used to generate generic models of the biocomposite with different aspect ratios, the data collected was then used to compute the respective Young’s Modulus and a stress analysis based on Mohr’s theory was carried out on one of the models using the ANSYS post-processor. The simulated biocomposite was found to have Young’s Modulus and tensile strength of approximately 21.1 GPa and 142.5 MPa respectively which closely resembles the actual properties of human cortical bones. However, there is a need to improve the mechanical strength of the biocomposite and some of the methods will be discussed in this report.